Natural IgG antibodies provide innate protection against ficolin-opsonized bacteria - Panda, Saswati (2015)
For nearly five decades since its discovery, the role of natural IgG, which pre‐exists in neonates and uninfected individuals, has remained unclear due to the general perception that natural antibodies lack affinity for pathogens. Here, we show for the first time that natural IgG recognizes a spectrum of bacteria through lectins like ficolin and mannose binding lectin (MBL). Infection‐inflammation condition markedly increased the affinity of natural IgG for bacteria associated with ficolins. After opsonization with IgG:ficolin complex, the bacteria were phagocytosed by monocytes via FcγRI. Infection of C3−/− mice indicated that the natural IgG‐mediated immune complex was formed independently of C3. AID−/− mice lacking IgG were susceptible to infection, unless reconstituted with natural IgG. Thus, we have proven that natural IgG is not quiescent; rather, it plays a vital and immediate role in immune defense. Our findings provide a fresh perspective on natural antibodies, opening new avenues to explore host–microbe interaction.